2020
DOI: 10.1103/physrevb.102.064416
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cavity magnon polaritons

Abstract: We predict magnon-polariton states circulating unidirectionally in a microwave cavity when loaded by a number of magnets on special lines. Realistic finite-element numerical simulations, including dielectric, timedependent, and nonlinear effects, confirm the validity of the approximations of a fully analytical input-output model. We find that a phased antenna array can focus all power into a coherent microwave beam with controlled direction and an intensity that scales with the number of magnets.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The long-range dipolar interaction emitted from the excited nanomagnet can chirally couple with the traveling magnons of extended films as its rotation direction is locked to its momentum [28][29][30][31][32]. The microwaves show polarization-momentum locking when confined by the waveguide [33][34][35][36], cavity [37,38], or antenna [39][40][41], which were employed to realize the nonreciprocal magnon-photon coupling. With chiral coupling, the unidirectional traveling waves are excited by the nearby magnet in half-space [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The long-range dipolar interaction emitted from the excited nanomagnet can chirally couple with the traveling magnons of extended films as its rotation direction is locked to its momentum [28][29][30][31][32]. The microwaves show polarization-momentum locking when confined by the waveguide [33][34][35][36], cavity [37,38], or antenna [39][40][41], which were employed to realize the nonreciprocal magnon-photon coupling. With chiral coupling, the unidirectional traveling waves are excited by the nearby magnet in half-space [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…These methods seek to integrate the domain knowledge of decision-makers in a structured manner, identifying a handful of scenarios that probe key known uncertainties. 35,36 In air quality management, Scenario Planning methods have the potential to complement traditional control-versusbaseline policy analysis by producing a small set of very different alternative baselines. The scenarios provide distinct combinations of variables in the decision space that can be explored further with Monte Carlo analysis or other methods to propagate input parameter uncertainty.…”
Section: Methods For Addressing Uncertaintymentioning
confidence: 99%
“…1 H NMR (500 MHz, DMSO-d 6 ): δ 7.91 2H),3H),6.71 (s,1H),3H),2H),1.86 (dddd,J = 13.4,9.3,6.6,5.4 Hz,1H),1H) 9, 170.8, 156.2, 144.2, 141.1, 138.4, 128.11, 127.6, 127.5, 125.8, 125.7, 122.0, 121.6, 121.4, 120.6, 119.6, 66.4, 60.2, 53.4, 47.0, 31.7, 28. Peptides, and Protein Expression and Purification. 35,36 Wild-type human β-catenin (residues 138-781) were cloned into a pET-28b vector carrying a C-terminal 6× histidine (Novagen) and transformed into Escherichia coli BL21 DE3 (Novagen). Cells were cultured in LB medium with 30 μg/mL kanamycin until the OD 600 was approximately 0.8.…”
Section: Experimental Section Chemical Synthesismentioning
confidence: 99%
“…Further biological studies indicated that the formation of the β-catenin/Tcf complex in the cell nucleus is the penultimate step of the catenin/Tcf PPI using different strategies. [35][36][37] By targeting the Tcf4 G 13 ANDE 17 binding site, selective small-molecule inhibitors for β-catenin/Tcf PPI have been synthesized. 36 The best compound 1 (UU-T02) disrupted β-catenin/Tcf PPI with a K i of 1.36 μM in the fluorescence polarization (FP) competitive inhibition assay and displayed 175-and 64-fold selectivity over β-catenin/E-cadherin and β-catenin/APC, respectively.…”
Section: Introductionmentioning
confidence: 99%